The Influence of Socioeconomic Status, Income Expectations, and the Environment on Entrepreneurial Interest - Adristi Ardelia Hanifah; Abdullah Rifqi Zahron (Journal of Management and Digital Business, 2025)
Purpose – This study aims to examine and analyze the influence of socioeconomic status, income expectations, and environment on entrepreneurial interest. In addition, this study is important to conduct because entrepreneurship creates jobs, encourages innovation, and in education can help not only create graduates who are only job seekers but also create job opportunities. Design/methodology/approach – This research was conducted at Sekolah Tinggi Ilmu Ekonomi Tri Bhakti using quantitative research methods. Data were obtained through distributing questionnaires to 70 respondents using the snowball sampling method. Data analysis was carried out using SEM-PLS (Partial Least Squares) to test the relationship between variables because it is suitable for research on complex variables and data that has its own characteristics.  Findings – The results of the study indicate that socioeconomic status has a positive effect on entrepreneurial interest. Meanwhile, income expectations have a significant positive effect on entrepreneurial interest. The environment also shows a positive and significant effect on entrepreneurial interest. This study provides benefits for the Sekolah Tinggi Ilmu Ekonomi Tri Bhakti because it can foster entrepreneurial interest and encourage students to start businesses. And this study also provides benefits for the government to reduce unemployment and advance the economy. Limitations/Research Implications – The limitations of this study are that the variables are measured using a questionnaire, so the data obtained are the respondents perceptions. Respondents were obtained via Whatsapp so that the questionnaires obtained were not guided in detail in filling them out. Therefore, there may be the possibility of respondent subjectivity to the questions asked and also have obstacles in waiting for confirmation from respondents.